Does Parental Unemployment Cause Right-Wing Extremism? - Thomas Siedler (Deutsches Institut für Wirtschaftsforschung (DIW), 2007)
Recent years have witnessed a rise in right-wing extremism among German youth and young adults. This paper investigates the extent to which the experience of parental unemployment during childhood affects young people's far right-wing attitudes and xenophobia. Estimates from three German data sets show a positive relationship between growing up with unemployed parents and right-wing extremism, with xenophobia in particular. This paper uses stark dierences in unemployment levels between East and West Germany, both before and after reunification, to investigate a causal relationship. Instrumental variables estimates suggest strong and significant effects of parental unemployment on right-wing extremism. Various panel estimates also point to a positive relationship. The results are consistent with classical theories of economic interest and voting behavior which predict that persons who develop feelings of economic insecurity are more susceptible to right-wing extremism and anti-foreign sentiments.
Keywords: P16; J6; D72; C23; 330; Right-wing extremism; unemployment; instrumental variables estimations; panel estimators; intergenerational links; Radikalismus; Faschismus; Jugendliche; Familiensoziologie; Arbeitslosigkeit; Deutschland; Alte Bundesländer; Neue Bundesländer